Pengaruh Struktur Modal dan Bi Rate Terhadap Nilai Perusahaan Pada PT Bank Mega TBK - Nunik Tri Wulandari; M. Rimawan (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2021)
This study was aimed to reveal whether or not the effect of modal structure and BI Rate of company’s value in PT Bank Mega Tbk. The type study is associative research. The population was the financial data report of PT Bank Mega Tbk which accessed by www.idx.co.id in financial balance report from 2101 to 2019. This research used purposive sampling method. The technique of analysis data used multiple regression analysis couple with the classic assumption testing of normalities, multicolinearity tests, heterosticity tests, autocoreeclation tests, and regression model equations. Based on the result of this research shows that there is no significant effect of modal structure and negative to company’s value while BI Rate also is no significant and the result is positive to company’s value of PT Bank Mega Tbk